Wireless Power Transfer Impact on Data Channel - Baikova, Elena N. (2017)
Trabalho apresentado no 23rd International Symposium on Power Electronics, Electrical Drives, Automation and Motion (Speedam, 2016), 22-24 junho de 2016, Capri, Itália